Congenital diaphragmatic hernia in a 2-year-old resembling a tension pneumothorax - Yoonyoung Yves Choi; Aoife Bridget Rice; Roy Mark Kimble (Elsevier, 2019)
This case presents a child with a late presentation of a congenital diaphragmatic hernia in extremis with features suggestive of tension pneumothorax. Keywords: Congenital diaphragmatic hernia gastrothorax pneumothorax